Marriage and Consent in Pre-Tridentine Venice: Between Lay Conception and Ecclesiastical Conception, 1420-1545 - Cristellon, Cecilia (The sixteenth century journal, 2008)
The main sources of this article are 750 matrimonial trials discussed before the ecclesiastical court in Venice (1420-1545). This article analyzes the differing conceptions of marriage held by the laity and by the ecclesiastical hierarchy as these ideas were expressed in a dialectical relationship in court. Central to this analysis is the concept of consent, since consent, with widely differing interpretations, formed the foundation and the essence of both canonical and lay customary marriage. In the pre-Tridentine ecclesiastical court, custom played a leading role in deciding matters related to the marriage bond. These sources allow access to aspects of marriage that are usually not recorded and make it possible to reevaluate social phenomena which have been defined from a post-Tridentine perspective as transgressive. Practices such as bigamy, concubinage, and stuprum appear not as deviant, but as part of socially accepted marital behavior that is much broader and more heterogeneous than historians have appreciated.